Where to draw the line when the lines are blurred: A computational and functional analysis of cohesion in superhero comics. (December 2021) - Gahman, Paul
Highlights: Deixis, endophora and lexical repetition were most frequent cohesive ties. Narrative stage shift, ellipsis, exophora frequently broke cohesion. Identified delayed cohesion structures possibly unique to comics. Cohesion established and maintained through reciprocal nature of image and text. Abstract: With Halliday and Hasan's (1976) discussion of cohesion in text, linguists have long established the relation between cohesive devices employed, discursive context and register (González 2013; Guijarro 2016 ). However, cohesion studies in the realm of comics have largely revolved around the visual alone so far (Groensteen 2007; Kress & van Leeuwen 1996). Further, the question of how cohesive devices are employed in comics so as to attain specific discursive functions both as a reflection of the genre and as a multimodal medium remains unexplored. Based upon Halliday & Hasan's treatment of cohesion, the present research therefore addresses these deficits by examining cohesion in 20 Marvel and 21 DC modern-era comics, comprising a corpus totaling 70, 865 words (tokens) and 9, 805 lexemes (word types). Where cohesion was maintained, personal deixis (38.59%), endophora (12.80%), lexical repetition (11.11%) and discourse deixis (10.32%) were the most frequent ( fi  ≥  10%) cohesive ties. In incohesive sentences, the cohesion breaks could be attributed to changes in narrative stage (16.85%), ellipsis (12.68%), exophora (12.08%) and so-called delayed cohesion (11.53%), whereby cohesion amongst a series of sentences is interrupted by topic digressions or prefaces beyond the discursive context but immediately re-established thereafter. These findings illuminate the multimodal interdependency between text and image in superhero comics and its effect on realizing and resolving (non–)cohesive language.